Immigrant women's food choices in pregnancy: perspectives from women of Chinese origin in Canada. Issue 5 (4th July 2018) - Higginbottom, Gina Marie Awoko; Vallianatos, Helen; Shankar, Janki; Safipour, Jalal; Davey, Christina
ABSTRACT: Objective: Following migration, pregnant immigrant women may encounter social, cultural, and economic challenges that negatively affect their food choices and subsequent health outcomes. Culturally appropriate health care is crucial during the perinatal period to ensure the health of immigrant mothers and their children. This project aims to explore and understand how the health beliefs and practices of Chinese immigrant women affect their food choices during the perinatal period. Design: This qualitative study used the methodology of focused ethnography. Women participated in one semi-structured interview, followed by a second photo-assisted, semi-structured interview which incorporated photographs taken by the women themselves. Results: The food choices and health behaviors of immigrant women were influenced by their general health beliefs, cultural knowledge concerning particular types of foods, traditional Chinese medical beliefs, social advice and information, and socio-economic factors. Conclusion: The provision of culturally appropriate health care is crucial during the perinatal period, as it is not only a vulnerable life stage for women and their children but also a sensitive period of interaction with the Canadian health-care system. Understanding these intersecting factors can help to ensure culturally appropriate care and optimized health outcomes for Chinese immigrant women during the perinatal period.